Promotion mix, MSMEs, Community Promotion Mix Sebagai Kunci Sukses HnD Cafe - Candra, Kane (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
HnD Cafe, a micro-MSME offering Manadonese drinks and specialties, faces the challenge of visibility and minimal exposure in the community. By considering the limitations of human resources and capital, the community service team seeks to carry out a promotion mix that includes Instagram Paid Promote, event sponsorship, and booth opening at the peak night of Manifest UMN to increase exposure to HnD Cafe. The results of community service show that this promotion mix has succeeded in increasing exposure and creating awareness of a sustainable HnD Café, strengthening the image of HnD Cafe, and increasing sales potential. Keywords: Promotion mix, MSMEs, Community Service